2010
DOI: 10.1111/j.1464-5491.2010.03161.x
|View full text |Cite
|
Sign up to set email alerts
|

The Chronic Kidney Disease Epidemiology Collaboration (CKD‐EPI) equation is less accurate in patients with Type 2 diabetes when compared with healthy individuals

Abstract: The CKD-EPI equation is less accurate in patients with Type 2 diabetes when compared with healthy individuals, with a 2.5-fold greater bias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 30 publications
3
66
2
1
Order By: Relevance
“…However, according to recent studies, these equations have a poor performance for patients with diabetes and markedly underestimate GFR (4,5). This disappointing performance seems to be associated with specific characteristics of the patients with diabetes, such as hyperglycemia, glomerular hyperfiltration, and obesity, which probably highlight the limitations of creatinine itself as a GFR marker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, according to recent studies, these equations have a poor performance for patients with diabetes and markedly underestimate GFR (4,5). This disappointing performance seems to be associated with specific characteristics of the patients with diabetes, such as hyperglycemia, glomerular hyperfiltration, and obesity, which probably highlight the limitations of creatinine itself as a GFR marker.…”
Section: Discussionmentioning
confidence: 99%
“…However, the accuracy of creatinine-based equations to estimate GFR, including the new Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation, has been questioned for patients with diabetes (4,5). Recently, Rognant et al (5) demonstrated that CKD-EPI presented a poor performance in diabetic patients with a wide range of renal function, working even worse than MDRD equation.…”
mentioning
confidence: 99%
“…Creatinine-based GFR estimating equations are more biased and less precise at normal to high GFR levels than cystatin-based estimates on both an absolute and percentage basis (17) and will likely lead to GFR slopes that are even more difficult to interpret, particularly when there are small numbers of observations or short follow-up periods. Therefore, the choice of GFR measure (or estimate) will undoubtedly influence which patients are considered to have RFD, affecting the predictive value of this measure.…”
Section: Discussionmentioning
confidence: 99%
“…Serum creatinine remains the principal variable of the GFR-estimating equations, and if it is not accurately representing the individual's muscular mass [70], there is little chance that including the creatinine into the equations would improve their performance. Classical examples are hyperfiltrating diabetic patients [49,59,71] and cirrhotic [72,73], renal transplanted [21,51,55], elderly [21,73] and anorectic patients [73].…”
Section: Co N C L U S I O N : P O P U L At I O N V E R S U S P At I Ementioning
confidence: 99%